173 Long Term Analysis of The Evolution of Practice and Results of Abdominal Wall Reconstruction by A Single Surgeon. (12th October 2021) - Woffenden, H; Vijayan, D; Stevens, E; Ghini, F; Cunha, M; Suggett, N
Abstract: Background: It is estimated that at least 12-15% of abdominal operations lead to incisional hernias, and Worldwide, evidence shows high rates of recurrence after surgical repair ranging from 12.7% in the Danish hernia registry to 23% in the Swedish registry. Method: This is a retrospective analysis of the practice of a single surgeon at a tertiary centre. An electronic database provided all hernia surgeries done by the surgeon. A total of 185 patients with complete data were included who had open hernia repair. Electronic patient records were analysed to collect the data. Results: 185 patients, with a median age of 57 years (IQR 68 – 49), and BMI of 31.14 (IQR 36.02 – 27.52), had a hernia recurrence rate of 15.6% (29/185). More than 80% of the cases were complex hernias with a European Hernia classification of M3 and/ or W3, with dense intestinal adhesions and multiple previous repairs. Variability in techniques and mesh evolved over this period, from anterior component separation to transversus abdominis release to achieve closure of the abdomen. Polypropylene meshes were used for non-contaminated or less complex cases. The use of biologics in the early years has been superseded by biosynthetic. Conclusions: The creation of the abdominal wall unit and subsequent MDT at this centre resulted in a rise of total procedures, complexity of cases and patients with significant co-morbidities. Specialised abdominal wall surgeons are associated with better results when performing complex abdominal wall reconstructions.